Elements of shipping - Branch, Alan E. (Routledge, 2007)
Containing chapters on seaports and electronic data interchange, this book explains various elements of shipping such as operating, e-commerce/computerization, commercial, legal, economic, technical, managerial, logistics and financial considerations. It is useful for shipping executives, students and academics with interest in shipping industry